Earlier Onset and Expanded Seasonality of Sub-Regulatory Dissolved Oxygen Levels in Embayments of Buzzards Bay, Massachusetts - Kristin Huizenga; Christopher Neill; Rachel W. Jakuba; Jennie E. Rheuban; Tony Williams (Estuaries and Coasts, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

A meaningful performative experience: using Forum Theatre as an ethical method in sustainability science - María Mancilla García; Lena Bertemes Lalia; Marlino Mubai; Tilman Hertz; Elizabeth Maria Drury O’Neill; Caroline Abunge; Salomão Olinda Bandeira; François Bousquet; Christopher Cheupe; Dadivo José Combane; Tim Daw; Nyawira Muthiga; et al. (Sustainability Science, 2025)
Sustainability scientists have engaged in extensive discussions on ethical ways of doing research and argued on the importance of co-production approaches to counter knowledge extractivism. The specific issue of research fatigue, often associated with knowledge extractivism, and the possible methods to counter it, have however received less attention. This paper seeks to contribute to discussions on ethical ways of doing research by focusing on our experience of using theatre, specifically, Forum Theatre, to investigate divergent perceptions of environmental change and related tensions among selected coastal communities in Kenya and Mozambique. We argue that Forum Theatre constitutes an ethical method for sustainability scientists for four reasons: (i) it allows to co-produce knowledge with participants; (ii) it facilitates horizontal exchange; (iii) it creates joyful moments; and (iv) it enables the transmission of skills that remain with participants beyond project durations. The paper engages with these four themes, first theoretically and then proposing a reflection based on our project experience. In the last section, we warn against some of the limitations of the approach.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Land-use change and deep-soil carbon distribution on the Brazilian Amazon-Cerrado agricultural frontier - Gustavo V. Popin; Maria Eduarda B. de Resende; Jorge L. Locatelli; Rafael S. Santos; Marcos Siqueira-Neto; Paulo M. Brando; Christopher Neill; Carlos E.P. Cerri (Agriculture, Ecosystems & Environment, 2025)

Frameworks and best practices for cumulative impact accounting in offshore energy development - Caitlin D. Kuempel; Jackson Stockbridge; Tess O’Neill; Laura L. Griffiths; Christopher L.J. Frid; Christopher J. Brown (Marine Policy, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Small molecule therapeutics for neutralising venom toxins – a drug discovery approach - Laura-Oana Albulescu; Adam Westhorpe; Amy Marriott; Rachel H. Clare; Emma Stars; Nada Mosallam; Daniel Chong-Jun-Weng; Ramachandran Gunasekar; Charlotte A. Dawson; Christopher Woodley; Nivya James; Rohit Patel; et al. (Toxicon, 2024)

Economic evaluations of urban green and blue space interventions: A scoping review - Christopher Tate; Ngan Tran; Alberto Longo; John Barry; Tim Taylor; Ciaran O'Neill; Ruth Hunter (Ecological Economics, 2024)

Assessing colostral and serum immunoglobulin G in alpacas using Brix refractometry and total serum protein - Amber K. O’Neill; Christopher E. Petzel; Joanne H. Connolly; Jane L. Vaughan; Randi Rotne (Veterinary Research Communications, 2024)
The adequate transfer of passive immunity is a critical factor in neonatal development and survivability. Although well documented in the dairy and equine industries, the recognition of inadequate immunoglobulin transfer on-farm and its impact on the ability of alpaca cria to thrive is largely unknown. Colostrum samples were collected from female alpaca within 24 h of parturition by the owners and whole blood collected from cria by the investigators between 1 and 7 days of age. Direct IgG concentration of milk and serum was determined using radial immunodiffusion assay (RID) and was indirectly estimated using optical and digital Brix refractometry for total solids and clinical refractometry for total serum protein. There was a strong correlation between optical and digital Brix refractometry, and colostral IgG concentration determined by RID. There was a moderate correlation between serum IgG concentration determined by RID and total serum protein in crias. Optical and digital Brix refractometry for colostral IgG estimation and total serum protein for serum IgG estimation are reliable, accurate and easy-to-use tools that can be used on-farm by trained, competent technicians to assess a failure of passive transfer in alpacas. A pilot study at one property only was performed, due to COVID-19 travel restriction interference. Further research is required to determine the reference intervals for these tools to be practical.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Woody Plant–Soil Relationships in Interstitial Spaces Have Implications for Future Forests Within and Beyond Urban Areas - Gisselle A. Mejía; Peter M. Groffman; Meghan L. Avolio; Anika R. Bratt; Jeannine Cavender-Bares; Noortje H. Grijseels; Sharon J. Hall; James Heffernan; Sarah E. Hobbie; Susannah B. Lerman; Jennifer L. Morse; Desiree L. Narango; et al. (Ecosystems, 2024)

Trajectories of plant communities in Massachusetts, USA cranberry farms discontinued from agriculture - Christopher Neill; Anastasia M. Pulak; Haley J. Miller; Benjamin R. Hoekstra; Sarah M. Klionsky (Wetlands Ecology and Management, 2023)
Retirement of cultivated croplands creates potential for ecosystem and wetland restoration, but vegetation and soil legacies of cropping influence the development of post-agriculture vegetation. In low-lying coastal watersheds of southeastern Massachusetts, cranberries ( Vaccinium macrocarpon Aiton) are cultivated in commercial farm units that are diked, leveled and sanded beds created from historic wetlands. Current low cranberry prices and expanding cranberry production elsewhere now increase the likelihood of cranberry farmland retirement. We quantified the trajectories of plant species richness and cover, and plant characteristics (life form, native or non-native, wetland or non-wetland) in a chronosequence of cranberry farm beds that ranged from cultivated units to those retired from cropping and revegetated for 90 years with no post-cropping management. Species richness increased from active beds to 10–20 year-old beds and subsequently decreased. Post-retirement species richness was overwhelmingly dominated by native species. Shrub and tree richness and cover increased steadily over time. The richness of wetland, upland and facultative species all increased quickly after retirement and then declined in the oldest retired beds. The basal area and canopy cover of red maple ( Acer rubrum ) and pitch pine ( Pinus rigida ) increased over time. Vegetation followed a relatively consistent successional trajectory and the plant community after five to nine decades was predominantly forest and dominated by non-wetland plants. Encouragement of long-term persistence of greater diversity and cover of wetland plant species on retired cranberry farms will likely require active hydrological and soil modifications that decrease sand depth and raise water tables.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Anion Exchange Capacity Explains Deep Soil Nitrate Accumulation in Brazilian Amazon Croplands - Alexandra Huddell; Christopher Neill; Cheryl A. Palm; Darlisson Nunes; Duncan N. L. Menge (Ecosystems, 2023)
Deep tropical soils with net anion exchange capacity can adsorb nitrate and might delay the eutrophication of surface waters that is often associated with many temperate croplands. We investigated anion exchange capacity and soil nitrate pools in deep soils in the Southern Brazilian Amazon, where conversion of tropical forest and Cerrado to intensive fertilized soybean and soybean-maize cropping expanded rapidly in the 2000s. We found that mean soil nitrate pools in the top 8 m increased from 143 kg N ha −1 in forest to 1,052 in soybean and 1,161 kg N ha −1 in soybean-maize croplands. This nitrate accumulation in croplands aligned with the estimated N surpluses in the croplands. Soil anion exchange capacity explained the magnitude of nitrate accumulation. High nitrate retention in soils was consistent with current low levels of streamwater nitrate exported from croplands. Soil exchange sites were far from saturation, which suggests that nitrate accumulation can continue for longer under current cropping practices, although mechanisms such as competition with other anions and preferential water flowpaths that bypass exchange sites could reduce the time to saturation.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Undeveloped and developed phases in the centennial evolution of a barrier-marsh-lagoon system: The case of Long Beach Island, New Jersey - Christopher Tenebruso; Shane Nichols-O’Neill; Jorge Lorenzo-Trueba; Daniel J. Ciarletta; Jennifer L. Miselis (Frontiers in Marine Science, 2022)
Barrier islands and their associated backbarrier environments protect mainland population centers and infrastructure from storm impacts, support biodiversity, and provide long-term carbon storage, among other ecosystem services. Despite their socio-economic and ecological importance, the response of coupled barrier-marsh-lagoon environments to sea-level rise is poorly understood. Undeveloped barrier-marsh-lagoon systems typically respond to sea-level rise through the process of landward migration, driven by storm overwash and landward mainland marsh expansion. Such response, however, can be affected by human development and engineering activities such as lagoon dredging and shoreline stabilization. To better understand the difference in the response between developed and undeveloped barrier-marsh-lagoon environments to sea-level rise, we perform a local morphologic analysis that describes the evolution of Long Beach Island (LBI), New Jersey, over the last 182 years. We find that between 1840 and 1934 the LBI system experienced landward migration of all five boundaries, including 171 meters of shoreline retreat. Between the 1920s and 1950s, however, there was a significant shift in system behavior that coincided with the onset of groin construction, which was enhanced by beach nourishment and lagoon dredging practices. From 1934 to 2022 the LBI system experienced ~22 meters of shoreline progradation and a rapid decline in marsh platform extent. Additionally, we extend a morphodynamic model to describe the evolution of the system in terms of five geomorphic boundaries: the ocean shoreline and backbarrier-marsh interface, the seaward and landward lagoon-marsh boundaries, and the landward limit of the inland marsh. We couple this numerical modeling effort with the map analysis during the undeveloped phase of LBI evolution, between 1840 and 1934. Despite its simplicity, the modeling framework can describe the average cross-shore evolution of the barrier-marsh-lagoon system during this period without accounting for human landscape modifications, supporting the premise that natural processes were the key drivers of morphological change. Overall, these results suggest that anthropogenic effects have played a major role in the evolution of LBI over the past century by altering overwash fluxes and marsh-lagoon geometry; this is likely the case for other barrier-marsh-lagoon environments around the world.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

An inter-laboratory comparison of an NLRP3 inflammasome activation assay and dendritic cell maturation assay using a nanostructured lipid carrier and a polymeric nanomedicine, as exemplars - Rob J. Vandebriel; Christopher A. W. David; Jolanda P. Vermeulen; Neill J. Liptrott (Drug Delivery and Translational Research, 2022)
Nanoparticles including nanomedicines are known to be recognised by and interact with the immune system. As these interactions may result in adverse effects, for safety evaluation, the presence of such interactions needs to be investigated. Nanomedicines in particular should not unintendedly interact with the immune system, since patient’s exposure is not minimised as in the case of ‘environmental’ nanoparticles, and repeated exposure may be required. NLRP3 inflammasome activation and dendritic cell (DC) maturation are two types of immune mechanisms known to be affected by nanoparticles including nanomedicines. NLRP3 inflammasome activation results in production of the pro-inflammatory cytokines IL-1β and IL-18, as well as a specific type of cell death, pyroptosis. Moreover, chronic NLRP3 inflammasome activation has been related to several chronic diseases. Upon maturation, DC activate primary T cells; interference with this process may result in inappropriate activation and skewing of the adaptive immune response. Here, we evaluated the effect of two nanomedicines, representing nanostructured lipid carriers and polymers, on these two assays. Moreover, with a view to possible future standardisation and regulatory application, these assays were subject to an inter-laboratory comparison study using common SOPs. One laboratory performed three independent NLRP3 inflammasome activation experiments, while the other performed a single experiment. Two laboratories each performed three independent DC maturation experiments. While the nanostructured lipid carrier only showed marginal effects, the polymers showed major cytotoxicity. No evidence for inflammasome activation or DC maturation was demonstrated. Intra- and inter-laboratory comparison showed clearly reproducible results. Graphical abstract

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Molybdenum, phosphorus, and pH do not constrain nitrogen fixation in a tropical forest in the southeastern Amazon - Michelle Y. Wong; Christopher Neill; Roxanne Marino; Divino Silvério; Robert W. Howarth (Ecology, 2021)
High rates of biological nitrogen fixation (BNF) are commonly reported for tropical forests, but most studies have been conducted in regions that receive substantial inputs of molybdenum (Mo) from atmospheric dust and sea‐salt aerosols. Even in these regions, the low availability of Mo can constrain free‐living BNF catalyzed by heterotrophic bacteria and archaea. We hypothesized that in regions where atmospheric inputs of Mo are low and soils are highly weathered, such as the southeastern Amazon, Mo would constrain BNF. We also hypothesized that the high soil acidity, characteristic of the Amazon Basin, would further constrain Mo availability and therefore soil BNF. We conducted two field experiments across the wet and dry seasons, adding Mo, phosphorus (P), and lime alone and in combination to the forest floor in the southeastern Amazon. We sampled soils and litter immediately, and then weeks and months after the applications, and measured Mo and P availability through resin extractions and BNF with the acetylene reduction assay. The experimental additions of Mo and P increased their availability and the lime increased soil pH. While the combination of Mo and P increased BNF at some time points, BNF rates did not increase strongly or consistently across the study as a whole, suggesting that Mo, P, and soil pH are not the dominant controls over BNF. In a separate short‐term laboratory experiment, BNF did not respond strongly to Mo and P even when labile carbon was added. We postulate that high nitrogen (N) availability in this area of the Amazon, as indicated by the stoichiometry of soils and vegetation and the high nitrate soil stocks, likely suppresses BNF at this site. These patterns may also extend across highly weathered soils with high N availability in other topographically stable regions of the tropics.

Land use changes in Southeastern Amazon and trends in rainfall and water yield of the Xingu River during 1976–2015 - Rodnei Rizzo; Andrea S. Garcia; Vívian M. de F. N. Vilela; Maria Victoria R. Ballester; Christopher Neill; Daniel C. Victoria; Humberto R. da Rocha; Michael T. Coe (Climatic Change, 2020)

Woody plant encroachment into coastal grasslands: consequences for soil properties and plant diversity - Eva Kinnebrew; Lena K. Champlin; Gillian L. Galford; Christopher Neill (Regional Environmental Change, 2020)

Biological Nitrogen Fixation Does Not Replace Nitrogen Losses After Forest Fires in the Southeastern Amazon - Michelle Y. Wong; Christopher Neill; Roxanne Marino; Divino V. Silvério; Paulo M. Brando; Robert W. Howarth (Ecosystems, 2020)

Meta‐analysis on the potential for increasing nitrogen losses from intensifying tropical agriculture - Alexandra M. Huddell; Gillian L. Galford; Katherine L. Tully; Cynthia Crowley; Cheryl A. Palm; Christopher Neill; Jonathan E. Hickman; Duncan N. L. Menge (Global Change Biology, 2020)
Fertilized temperate croplands export large amounts of reactive nitrogen (N), which degrades water and air quality and contributes to climate change. Fertilizer use is poised to increase in the tropics, where widespread food insecurity persists and increased agricultural productivity will be needed, but much less is known about the potential consequences of increased tropical N fertilizer application. We conducted a meta‐analysis of tropical field studies of nitrate leaching, nitrous oxide emissions, nitric oxide emissions, and ammonia volatilization totaling more than 1,000 observations. We found that the relationship between N inputs and losses differed little between temperate and tropical croplands, although total nitric oxide losses were higher in the tropics. Among the potential drivers we studied, the N input rate controlled all N losses, but soil texture and water inputs also controlled hydrological N losses. Irrigated systems had significantly higher losses of ammonia, and pasture agroecosystems had higher nitric oxide losses. Tripling of fertilizer N inputs to tropical croplands from 50 to 150 kg N ha −1 year −1 would have substantial environmental implications and would lead to increases in nitrate leaching (+30%), nitrous oxide emissions (+30%), nitric oxide (+66%) emissions, and ammonia volatilization (+74%), bringing tropical agricultural nitrate, nitrous oxide, and ammonia losses in line with temperate losses and raising nitric oxide losses above them.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Evaluating Current Practices in Shelf Life Estimation - Robert Capen; David Christopher; Patrick Forenzo; Kim Huynh-Ba; David LeBlond; Oscar Liu; John O’Neill; Nate Patterson; Michelle Quinlan; Radhika Rajagopalan; James Schwenke; Walter Stroup (AAPS PharmSciTech, 2018)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Dissolved Organic and Inorganic Carbon Flow Paths in an Amazonian Transitional Forest - Vania Neu; Nicholas D. Ward; Alex V. Krusche; Christopher Neill (Frontiers in Marine Science, 2016)

Flexibility of ephemeral wetland crustaceans: environmental constraints and anthropogenic impacts - Brian J. O’Neill; D. Christopher Rogers; James H. Thorp (Wetlands Ecology and Management, 2016)

Metagenetic analysis of patterns of distribution and diversity of marine meiobenthic eukaryotes - Vera G. Fonseca; Gary R. Carvalho; Ben Nichols; Christopher Quince; Harriet F. Johnson; Simon P. Neill; John D. Lambshead; W. Kelley Thomas; Deborah M. Power; Simon Creer (Global Ecology and Biogeography, 2014)
Aim Meiofaunal communities that inhabit the marine benthos offer unique opportunities to simultaneously study the macroecology of numerous phyla that exhibit different life‐history strategies. Here, we ask: (1) if the macroecology of meiobenthic communities is explained mainly by dispersal constraints or by environmental conditions; and (2) if levels of meiofaunal diversity surpass existing estimates based on morphological taxonomy. Location UK and mainland European coast. Methods Next‐generation sequencing techniques ( NGS ; R oche 454 FLX platform) using 18S nuclear small subunit ribosomal DNA ( rDNA ) gene. Pyrosequences were analysed using A mplicon N oise followed by chimera removal using P erseus . Results Rarefaction curves revealed that sampling saturation was only reached at 15% of sites, highlighting that the bulk of meiofaunal diversity is yet to be discovered. Overall, 1353 OTU s were recovered and assigned to 23 different phyla. The majority of sampled sites had c. 60–70 unique operational taxonomic units ( OTU s) per site, indicating high levels of beta diversity. The environmental parameters that best explained community structure were seawater temperature, geographical distance and sediment size, but most of the variability ( R 2 = 70%–80%) remains unexplained. Main conclusions High percentages of endemic OTU s suggest that meiobenthic community composition is partly niche‐driven, as observed in larger organisms, but also shares macroecological features of microorganisms by showing high levels of cosmopolitanism (albeit on a much smaller scale). Meiobenthic communities exhibited patterns of isolation by distance as well as associations between niche, latitude and temperature, indicating that meiobenthic communities result from a combination of niche assembly and dispersal processes. Conversely, isolation‐by‐distance patterns were not identified in the featured protists, suggesting that animals and protists adhere to radically different macroecological processes, linked to life‐history strategies.

Ecosystem legacy of the introduced N2-fixing tree Robinia pseudoacacia in a coastal forest - Betsy Von Holle; Christopher Neill; Erin F. Largay; Katherine A. Budreski; Barbara Ozimec; Sara A. Clark; Krista Lee (Oecologia, 2013)

On the Shelf Life of Pharmaceutical Products - Robert Capen; David Christopher; Patrick Forenzo; Charles Ireland; Oscar Liu; Svetlana Lyapustina; John O’Neill; Nate Patterson; Michelle Quinlan; Dennis Sandell; James Schwenke; Walter Stroup; et al. (AAPS PharmSciTech, 2012)

Predator control promotes invasive dominated ecological states - Arian D. Wallach; Christopher N. Johnson; Euan G. Ritchie; Adam J. O’Neill (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1008–1018 Abstract Invasive species are regarded as one of the top five drivers of the global extinction crisis. In response, extreme measures have been applied in an attempt to control or eradicate invasives, with little success overall. We tested the idea that state shifts to invasive dominance are symptomatic of losses in ecosystem resilience, due to the suppression of apex predators. This concept was investigated in Australia where the high rate of mammalian extinctions is largely attributed to the destructive influence of invasive species. Intensive pest control is widely applied across the continent, simultaneously eliminating Australia’s apex predator, the dingo ( Canis lupus dingo ). We show that predator management accounts for shifts between two main ecosystem states. Lethal control fractures dingo social structure and leads to bottom‐up driven increases in invasive mesopredators and herbivores. Where control is relaxed, dingoes re‐establish top–down regulation of ecosystems, allowing for the recovery of biodiversity and productivity.

Nitrogen Transformations in Flowpaths Leading from Soils to Streams in Amazon Forest and Pasture - Joaquín Chaves; Christopher Neill; Sonja Germer; Sergio Gouveia Neto; Alex V. Krusche; Adriana Castellanos Bonilla; Helmut Elsenbeer (Ecosystems, 2009)

Alteration of water levels in a Massachusetts coastal plain pond subject to municipal ground-water withdrawals - Richard McHorney; Christopher Neill (Wetlands, 2007)

Soil Solution Nitrogen Losses During Clearing of Lowland Amazon Forest for Pasture - Christopher Neill; Marisa C. Piccolo; Carlos C. Cerri; Paul A. Steudler; Jerry M. Melillo (Plant and Soil, 2006)

Nitrogen dynamics during till and no-till pasture restoration sequences in Rondônia, Brazil - Janaina Braga do Carmo; Christopher Neill; Diana C. Garcia-Montiel; Marisa de Cássia Piccolo; Carlos C. Cerri; Paul A. Steudler; Cristiano Alberto de Andrade; Caio C. Passianoto; Brigitte J. Feigl; Jerry M. Melillo (Nutrient Cycling in Agroecosystems, 2005)

Rates and controls of nitrous oxide and nitric oxide emissions following conversion of forest to pasture in Rondônia - Christopher Neill; Paul A. Steudler; Diana C. Garcia-Montiel; Jerry M. Melillo; Brigitte J. Feigl; Marisa C. Piccolo; Carlos C. Cerri (Nutrient Cycling in Agroecosystems, 2005)

Net nitrogen mineralization and net nitrification rates in soils following deforestation for pasture across the southwestern Brazilian Amazon Basin landscape - Christopher Neill; Marisa C. Piccolo; Carlos C. Cerri; Paul A. Steudler; Jerry M. Melillo; Marciano Brito (Oecologia, 1997)